Analyzing the Reading Habits of Sports Faculty Students - KAYA, Leyla; ÖZMADEN, Murat; UĞUR, Oruç Ali (Sportif Bakış: Spor ve Eğitim Bilimleri Dergisi, 2020)
This study aimed to analyze the reading habits of Aydın Adnan Menderes University Faculty of Sports Science students according to age, gender, department and class. The data were collected in the 2019-20 Spring semester and 246 students participated in the study. In the study to collect data Reading Habits scale was used. Gömleksiz initially developed the scale in 2004. The scale has 6 factors and 31 items anchored with 5 Likert type scale. The data were evaluated with SPSS 23.0 for Windows using Pearson Correlation test in addition to Independent samples t test and One-way ANOVA at 95% confidence level. According to analyzed results low level negative correlations were found in the variable reading habits according to age. Besides, male participants had higher reading habit in some of the subdimensions. Lastly, sports management and second class students had better reading habits than the other department and class students.